2023
DOI: 10.3390/ijms24065925
|View full text |Cite
|
Sign up to set email alerts
|

Immune Regulatory Functions of Macrophages and Microglia in Central Nervous System Diseases

Abstract: Macrophages can be characterized as a very multifunctional cell type with a spectrum of phenotypes and functions being observed spatially and temporally in various disease states. Ample studies have now demonstrated a possible causal link between macrophage activation and the development of autoimmune disorders. How these cells may be contributing to the adaptive immune response and potentially perpetuating the progression of neurodegenerative diseases and neural injuries is not fully understood. Within this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 328 publications
(439 reference statements)
0
3
0
1
Order By: Relevance
“…It was reported that massive activation of microglia after rickettsial infection results in neurotoxicity and inflammation of the CNS, leading to the death of infected mice [12]. However, in the context of the published data, we suppose that microglia migrate to the site of neuronal damage and exert neuroprotective processes, as this is their authentic function in a diseased brain [39]. The recent review summarizes the pathogenesis of Rickettsia-infected mice and presents a set of upregulated genes coding for specific cytokines and indicates affected brain cells [14].…”
Section: Discussionmentioning
confidence: 76%
“…It was reported that massive activation of microglia after rickettsial infection results in neurotoxicity and inflammation of the CNS, leading to the death of infected mice [12]. However, in the context of the published data, we suppose that microglia migrate to the site of neuronal damage and exert neuroprotective processes, as this is their authentic function in a diseased brain [39]. The recent review summarizes the pathogenesis of Rickettsia-infected mice and presents a set of upregulated genes coding for specific cytokines and indicates affected brain cells [14].…”
Section: Discussionmentioning
confidence: 76%
“…При РС в качестве механизма повреждения ЦНС предполагается аберрантная стимуляция плазматических и В-клеток, приводящая к выработке аутоантител против специфических антигенов миелина. В экспериментах было показано, что взаимодействие В-лимфоцитов с CD4 + -Т-клетками инициирует адаптивный иммунный ответ на антигены миелина, а подавление В-клеточного иммунитета приводит к снижению воспаления и выраженности клинических проявлений [22,23]. Я.А.…”
Section: таблица 1 показатели клеточного иммунитета у обследованных б...unclassified
“…These pathways culminate in the activation of astrocytes and microglia in the CNS and the release of a variety of pro-inflammatory molecules, including cytokines, chemokines, ROS, and nitric oxide, via peripheral pro-inflammatory mediators to promote a local immune response and lead to neuroinflammation ( Ransohoff and Brown, 2012 ). Activated microglia can promote immune cell maturation through antigen presentation, and the latter secrete cytokines to promote glial cell activation, creating positive feedback of the immune response ( Poppell et al, 2023 ). Glutamate-glutamine cycling and metabolic homeostasis can influence cell interactions, inflammatory signaling activation, modulation of cellular excitability, and cell survival ( Zhang et al, 2022 ).…”
Section: Mechanisms By Which Peripheral Inflammation Promotes Central...mentioning
confidence: 99%